Augmented Reality for Vocabulary Learning and Speaking Skills of Tourism Employees - Umar, Umar; Yuliadi, Yuliadi; Hidayatullah, Muhammad; Rahman, A.; Hassan, Zainudin (Journal of Languages and Language Teaching, 2025)
This study explores the application of Augmented Reality (AR) technology as a tool to enhance environmental vocabulary learning and improve the speaking skills of tourism employees in Sumbawa. Given the importance of English proficiency in the tourism industry, many employees face challenges in mastering vocabulary and effective communication. Adopting a descriptive qualitative approach, data were collected through questionnaires and interviews with 16 employees from four tourism sites. The findings indicate that 87.5% of respondents believe AR significantly aids vocabulary expansion, with 75% reporting increased confidence in speaking English. Additionally, 62.5% see AR as relevant to their professional needs, while 50% find it helpful in understanding environmental terminology. Despite these benefits, some challenges remain, including limited access to AR devices and the absence of real-time feedback. The study concludes that AR has substantial potential to enhance language learning by improving vocabulary retention and speaking proficiency. Moreover, integrating AR into tourism training programs could further support employees in developing essential language skills for their professional growth.